Identification analysis of Plantacyanin (PLC) genes in Camellia sinensis and functional identification of CsPLC-3 in yeast. Issue 5 (2nd September 2020) - Han, Zhaolan; Ma, Yuanchun; Zhao, Yue; Qin, Hao; Li, Jinqiu; Zhou, Lin; Zhu, Xujun; Wang, Yuhua; Fang, Wanping
ABSTRACT: Plantacyanin ( PLC ) plays an important role in plant growth, development, and responses to metal cation stress. However, the function of PLC in tea remains unclear. In this study, three PLC genes were identified from the tea plant. Protein sequences and structure analyses indicated that the CsPLCs contained four conserved sites, and furthermore, promoter analysis showed that the genes were involved in growth and development, signal transduction, and stress responses of the tea plant. Quantitative real-time PCR analyses revealed that the CsPLCs exhibited organ-specific expression. CsPLC-1 was highly expressed in roots and stems, CsPLC-2 was highest expressed in stems, and CsPLC-3 in leaves. Additionally, Cu 2+, Al 3+, and NaCl stress strongly influence the expression of CsPLC-3 . Subcellular localisation assays revealed that CsPLC-3 was the plasma membrane and nuclear localised protein. Moreover, the CsPLC-3 gene enhanced Cu 2+, Al 3+, and NaCl tolerance in Saccharomyces cerevisiae and was significantly affected by pH.